27. EFFECTS OF SUPPLEMENTING COLOSCARE 24H 2+ ON NUTRITIONAL STATUS AND HEALTH OF KINDERGARTEN CHILDREN (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effectiveness of nutritional Coloscare 24h 2+ product supplementation on nutritional status and health of kindergarten children.Subject and method: The intervention study with a control group. Sample size: 120 children aged 36-59 months for each groups. The intervention group supplementing Coloscare 24h 2+ twice a day for 2 months, and the control group with a regular diet. The study was completed in Ninh Binh in February 2024. Data collection and analyze were according to research indicators and by SPSS20.0 software.Results: The rate of respiratory infection was lower 31.7% (5.8% compared to 37.5) (p
Keywords: Micronutrients, formula milk, height, weight, kindergarten children.